The Application of Swedish Massage to Reduce Peripheral Neuropathy Pain in Breast Cancer Clients with A History of Chemoterapy - Leni Karlina; Siti Mardhiyah Hermaningrum; Innez Karunia Mustikarani; Anggorowati (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Peripheral neuropathy pain is one of the manifestations of peripheral nervous system disorders in breast cancer clients with a history of chemotherapy. Peripheral neuropathy pain affects the daily activities and quality of life of breast cancer clients, even after chemotherapy treatment is completed. The purpose of this case study is to determine the effect of the application of Swedish massage on peripheral neuropathy pain of breast cancer clients. The method applied in this case study is descriptive research with a case study approach. The sampling technique in this case study used a non-probability sampling approach with purposive sampling method. The subjects used in this case study were three breast cancer clients with a history of chemotherapy who lived in the working area of the Ngesrep Community Health Center. Swedish massage intervention was implemented three times each week for two weeks with a 30 minutes duration on the foot and hand area that experienced peripheral neuropathy pain. The instrument used is the Numeric Rating Scale (NRS) questionnaire. Data were analyzed through narrative case reflections. The results of the case study showed a decrease in the scale and intensity of peripheral neuropathy pain in the three clients from moderate to mild. Swedish massage is expected to be applied independently and continuously as a supportive therapy, so that clients can be adaptive in managing peripheral neuropathy pain.